HADIS LEGAL MAXIMS KHIYĀR AL-MAJELIS MENURUT JOSEPH SCHACHT - Riady, Fahmi (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
According to Schacht, the study of legal maxims can be used as additional data to describe historically the growth of legal hadiths and the development of legal doctrine. The khiyār al-majelis hadith in the form of legal maxims can be placed in the context of this development. The focus of this study is Schacht's view regarding legal maxims hadiths, especially the khiyār al-majelis hadith. This article uses library research by using Joseph Schacht's work: The Origins as the main source. This research uses a qualitative-descriptive approach, with the documentary method as a data collection technique. The main problem in this study is analyzed historically-critically. The results of this research show that most legal maxims hadiths are a further development of the use of personal opinions and individual considerations of specialists and qāḍīs. The khiyār majelis hadith is an example of the process of developing legal doctrine in the form of legal maxims which later turned into hadith and have more complete isnād in classical colections. This last conclusion was refuted by A‘ẓamī who held the opposite view. And based on the results of the discussion, it seems that A‘ẓamī's criticism of Schacht's argument has not been very successful.